Improvement of Student Learning Outcomes Thru the Make a Match Learning Model on Biodiversity Material for 4th Grade Elementary School - Hesti Medisa Wulantika; Lasim Muzammil; Qomariyah (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the low science learning outcomes of fourth-grade students on the topic of Biodiversity, which is caused by the dominance of the lecture method that makes students passive. The purpose of this research is to improve the quality of the learning process and cognitive learning outcomes thru the Make a Match learning model. This research is a type of Classroom Action Research (CAR) with the research subjects being 20 fourth-grade students. The data collection techniques included learning outcome tests and observations of student activities. The data were analyzed using qualitative and quantitative techniques. The research procedure was carried out in two cycles, which included planning, implementation, observation, and reflection. The research results show a very significant improvement at each stage. At the pre-action stage, the average student score was only 53.5 with a classical completeness of 15% and increased to 73 with 65% completeness in Cycle I. In Cycle II, the average soared to 93 with 90% completeness, which falls into the "Very Good" category. Based on these results, it is concluded that the Make a Match learning model effectively improves learning outcomes in biodiversity material thru an interactive, enjoyable, and student-centered approach.